Płeć w miejscu pracy - rola kobiety we współczesnym zarządzaniu - Wiśniewska-Szałek, Agata (Gender in the workplace - the role of women in contemporary management, 2007)
Women on management positions, which were not previously available to their gender, have specific job status and opportunities of self-development. The author points out women’s values that are essential to succeed on management positions, highlighting women’s interpersonal skills as a crucial factor. Moreover, women’s management style is described as an efficient way to achieving success and a solution for modern women.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 202-212